1987
DOI: 10.1007/bf00284909
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the expression of aphidicolin-induced fragile sites in human lymphocyte cultures

Abstract: A correlation between specific fragile sites and cancer breakpoints has been suggested raising the question of fragile site expression as a predisposing factor in the occurrence of cancer in some persons. Before addressing the question of increased fragility among patients at high risk for cancer, we analyzed the variability of aphidicolin-induced fragile sites among nine normal persons and also among repeated samples from three of these individuals. Considerable variation in both the frequency and location of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…It is presently not conclusive whether any common fragile sites are expressed comparably with each other. Previous studies (Craig-Holmes et aL, 1987;Rao etal., 1988a, b;Fuster et al, 1989) sometimes exhibited individuals whose lymphocytes express other common fragile sites more frequently than fra(3)(pl4). Thus for the moment the findings obtained presently should be confined to be true for fra(3)(pl4).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is presently not conclusive whether any common fragile sites are expressed comparably with each other. Previous studies (Craig-Holmes et aL, 1987;Rao etal., 1988a, b;Fuster et al, 1989) sometimes exhibited individuals whose lymphocytes express other common fragile sites more frequently than fra(3)(pl4). Thus for the moment the findings obtained presently should be confined to be true for fra(3)(pl4).…”
Section: Discussionmentioning
confidence: 92%
“…Regarding this question, Craig-Holmes et aL (1987) observed that expression of common fragile sites by APC treatment was incompatible among three consecutive samplings from the same three persons. Smeets et aL (1986) also demonstrated that the expression of fra(3)(pl4) with the folate deficient condition was significantly disagreed between two consecutive samples in three of the six cases.…”
Section: Introductionmentioning
confidence: 99%
“…(1985); 8, Craig-Holmes et al (1987);9, Marlhens et aL (1986);10, Rao et al (1988). individuals in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Of the latter five, those at 4q34 and 6@2, both BrdU induced, were each found in only one individual, and thus need further confirmation. The site at 3q26.2, both folate sensitive and BrdU induced, has not been described, but a site at the adjoining band 3q27 has been reported (Glover, 1984;Yunis and Soreng, 1984;Craig-Holmes et al, 1987). The question of whether or not they are identical remains to be answered.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation